Proteomics analysis of high lipid-producing strain Mucor circinelloides WJ11: an explanation for the mechanism of lipid accumulation at the proteomic level. Issue 1 (December 2016) - Tang, Xin; Zan, Xinyi; Zhao, Lina; Chen, Haiqin; Chen, Yong; Chen, Wei; Song, Yuanda; Ratledge, Colin
Abstract Background The oleaginous fungus, Mucor circinelloides, is attracting considerable interest as it produces oil rich in γ-linolenic acid. Nitrogen (N) deficiency is a common strategy to trigger the lipid accumulation in oleaginous microorganisms. Although a simple pathway from N depletion in the medium to lipid accumulation has been elucidated at the enzymatic level, global changes at protein levels upon N depletion have not been investigated. In this study, we have systematically analyzed the changes at the levels of protein expression inM. circinelloides WJ11, a high lipid-producing strain (36 %, lipid/cell dry weight), during lipid accumulation. Results Proteomic analysis demonstrated that N depletion increased the expression of glutamine synthetase, involved in ammonia assimilation, for the supply of cellular nitrogen but decreased the metabolism of amino acids. Upon N deficiency, many proteins (e.g., fructose-bisphosphate aldolase, glyceraldehyde-3-phosphate dehydrogenase, enolase, pyruvate kinase) involved in glycolytic pathway were up-regulated while proteins involved in the tricarboxylic acid cycle (e.g., isocitrate dehydrogenase, succinyl-CoA ligase, succinate dehydrogenase, fumarate hydratase) were down-regulated, indicating this activity was retarded thereby leading to a greater flux of carbon into fatty acid biosynthesis. Moreover, glucose-6-phosphate dehydrogenase, transaldolase and transketolase, which participate in the pentose phosphate pathway, were up-regulated, leading to the increased production of NADPH, the reducing power for fatty acid biosynthesis. Furthermore, protein and nucleic acid metabolism were down-regulated and some proteins involved in energy metabolism, signal transduction, molecular chaperone and redox homeostasis were up-regulated upon N depletion, which may be the cellular response to the stress produced by the onset of N deficiency. Conclusion N limitation increased those expressions of the proteins involved in ammonia assimilation but decreased that involved in the biosynthesis of amino acids. Upon N deprivation, the glycolytic pathway was up-regulated, while the activity of the tricarboxylic acid cycle was retarded, thus, leading more carbon flux to fatty acid biosynthesis. Moreover, the pentose phosphate pathway was up-regulated, then this would increase the production of NADPH. Together, coordinated regulation of central carbon metabolism upon N limitation, provides more carbon flux to acetyl-CoA and NADPH for fatty acid biosynthesis.